2015
DOI: 10.11594/jtls.05.03.02
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization Compounds From Hexane and Ethyl Acetate Fractions of Peperomia pellucida L.

Abstract: Peperomia pellucida was used traditionally in Indonesia for health treatment: wounds, boils, pimples, abscesses, abdominal pain, colic, gout, kidney, rheumatic pain, fatigue headache, furuncles, conjunctivitis and anti dermatogenic and also for dengue treatment. The isolation compounds from hexane and ethyl acetate fractions of Peperomia pellucida L. are conducted by maceration of the dry herbs sample with methanol and partition with hexane, ethyl acetate, butanol and water. The hexane and ethyl acetate fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Leena and Annam [67] isolated a flavone glycoside from whole plant of P. pellucida and characterized the compound as vitexin by chromatographic and spectral analyses. The study carried out by Hartati et al [41] identified compounds viz. stigmasterol, analogue of pheophytin and β-sitosterol-D-glucopyranoside in the solvent extract of P. pellucida.…”
Section: Ethnobotanical Uses Of P Pellucidamentioning
confidence: 99%
“…Leena and Annam [67] isolated a flavone glycoside from whole plant of P. pellucida and characterized the compound as vitexin by chromatographic and spectral analyses. The study carried out by Hartati et al [41] identified compounds viz. stigmasterol, analogue of pheophytin and β-sitosterol-D-glucopyranoside in the solvent extract of P. pellucida.…”
Section: Ethnobotanical Uses Of P Pellucidamentioning
confidence: 99%
“…The warmed leaves are applied to sores and boils 7,31 and according to the Manila Medical Society, it is used to relieve arthritic pains, but it may cause Central Nervous System (CNS) depression 27 . In Indonesian traditional medicine, this plant is incorporated in the treatment of wounds, boils, abscesses, pimples, abdominal pain, colic, gout, rheumatic pain, fatigue, kidney disease, furuncles, eye inflammation (conjunctivitis), dengue 32 , and as an antihypertensive 33 . The crushed leaves are used to treat dizziness or headaches if the patient has a fever 28 .…”
Section: Ethnomedicinal Uses Of P Pellucida By Various Communities Amentioning
confidence: 99%
“…Bayma et al; 2000, had isolated a novel dimeric ArC2 compound named Pellucidin A, together with the known phenylpropanoid dillapiole from the methanol extract of aerial parts of P. pellucida. The isolation and characterization of the compounds from hexane and ethyl acetate fraction of ethanol extract had resulted in three compounds named stigmasterol, analogue pheophytin, and β-sitosterol-D-glucopyranoside 32 .…”
Section: Phytochemicals Present In P Pellucidamentioning
confidence: 99%
“…[5,6]. In addition to minerals, this plant also known to contain many bioactive substances such as stigma sterol, [7]; -amino acid,, alkaloid, glycoside, reducing sugar, flavonoid, tannin, steroid, terpenoid, neutral compound, phenolic compound and starch [8]; β-caryophyllene, αhumulene, epi-α-bisabolol, sabinene, crypt one and caryophyllene oxide. [9] In the city of Bandar Lampung, the capital of Lampung province, located in the southernmost part of Sumatra, this plant grows wild in the suburbs and is very easy to find.…”
Section: Introductionmentioning
confidence: 99%